2017
DOI: 10.3847/1538-4357/836/1/28
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectra of Hexa-peri-hexabenzocoronene Cations: HBC+ and HBC2+

Abstract: We present the first infrared (IR) gas-phase spectrum of a large and astronomically relevant polycyclic aromatic hydrocarbon (PAH) cation (C 42 H 18 + , HBC + ) and its dication (C 42 H 18 + 2 , HBC 2+ ). The spectra are recorded via infrared multiphoton dissociation (IRMPD) spectroscopy of ions stored in a quadrupole ion trap, using the intense IR radiation of a free electron laser in the 530-1800 cm −1 (5.6-18.9 μm) range. HBC + shows main intense absorption peaks at 762 (13.12), 1060 (9.43), 1192 (8.39), 12… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 48 publications
3
22
0
Order By: Relevance
“…Thus, if this is confirmed in other PAHs, these bands can offer a tool to identify PAHs with pentagon structures. Another pronounced difference is found around 1600 cm −1 ; whereas HBC + (Zhen et al 2017) only exhibits a relatively weak feature in this range, both DIP + an DC + have much stronger bands here. Further studies are required to assess whether this reflects the less symmetric structure of the species studied here, which could "activate" more CC modes than for the more highly symmetric HBC + .…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Thus, if this is confirmed in other PAHs, these bands can offer a tool to identify PAHs with pentagon structures. Another pronounced difference is found around 1600 cm −1 ; whereas HBC + (Zhen et al 2017) only exhibits a relatively weak feature in this range, both DIP + an DC + have much stronger bands here. Further studies are required to assess whether this reflects the less symmetric structure of the species studied here, which could "activate" more CC modes than for the more highly symmetric HBC + .…”
Section: Resultsmentioning
confidence: 75%
“…A comparison between Figures 2(A) and (B) shows clear differences. DIP + exhibits multiple CH in-plane bending vibration bands (1001, 1070, 1115, and 1152 cm −1 ) in a range (1000-1200 cm −1 ) where DC + , and also HBC + show only two resolved bands (Zhen et al 2017). The origin of these features can be traced back to a combination of CH in plane and CC stretches modes involving also, but not exclusively, the two pentagons in the DIP geometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutral and ionized PAHs present large differences in the relative intensities of their resulting IR spectra (Allamandola et al 1999;Tielens 2008). However, there is still no evidence for a unambiguous identification between singly and doubly charged PAHs in the ISM (Zhen et al 2017). The precise determination of the charge state of PAHs is a relevant astrophysical feature, which is also corroborated by our results.…”
Section: Multiple Ionization Of Pahs In Agnsmentioning
confidence: 99%
“…Infrared spectra of PAHs and PAH cations in the gas phase have also been reported (e.g., Joblin et al 1994;Oomens et al 2001Oomens et al , 2006. In earlier works we demonstrated that with our instrument for Photoprocessing of PAHs (i-PoP) connected to the free electron laser for infrared experiments (FELIX) we can record infrared multiphoton dissociation (IRMPD) spectra of large aromatic cations up to C 48 H •+ 20 (Zhen et al 2017(Zhen et al , 2018. Large sets of density functional theory (DFT) computed normal modes of PAHs have also been reported (e.g., Bauschlicher et al 2008Bauschlicher et al , 2009Ricca et al 2012).…”
Section: Introductionmentioning
confidence: 99%